2022
DOI: 10.1530/eje-22-0449
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting PEGylated growth hormone in children with idiopathic short stature

Abstract: Objective: To evaluate the safety and efficacy of weekly PEG-rhGH in children with idiopathic short stature (ISS) in China. Design and methods: A multicenter, phase II study randomized subjects 1:1:1 to weekly subcutaneous injections of PEG-rhGH 0.1 (low dose [LD]) or 0.2 mg/kg/week (high dose [HD]) or control for 52 weeks. The primary endpoint was change in HT-SDS from baseline to week 52. Secondary endpoints were height velocity (HV), bone maturity, IGF-1 SDS, and IGF-1/IGFBP-3 ratio. Results: A total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, there was no statistically significant difference in BA growth between the two groups ( P > 0.05). Study have reported no significant increase in BA after GH therapy[ 24 ], which might be due to the short treatment duration. Previous studies have shown that in adult GH deficiency, long-term rhGH replacement therapy induces an increase in bone mineral density, which is reflected in the lumbar spine and femoral neck, especially more pronounced in male patients[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was no statistically significant difference in BA growth between the two groups ( P > 0.05). Study have reported no significant increase in BA after GH therapy[ 24 ], which might be due to the short treatment duration. Previous studies have shown that in adult GH deficiency, long-term rhGH replacement therapy induces an increase in bone mineral density, which is reflected in the lumbar spine and femoral neck, especially more pronounced in male patients[ 25 ].…”
Section: Discussionmentioning
confidence: 99%